Perpaduan Metode Pembelajaran Al-Qur’an: Studi Analisis Metode Al-Baghdadi, Iqro’, Qiroati, Al-Tartil, dan Tilawati di Pondok Pesantren - Mirna Dewi; Muhammad Masyafa Alfauzi; Ahmad Adib Rifai; Tursila Tursila; Sujianto Sujianto; Yayuk Safitri; Tri Mir’atul Hasanah; Tias Asih; Susi Nawanti; Ana Uswatun Hidayah (KURAS Institute, 2022)
This research aims to explore the combination of Al-Qur'an learning methods utilized at Darul Ulum Seputih Banyak Islamic Boarding School. This pesantren employs five methods alternately: Al-Baghdadi, Iqro', Qiroati, Al-Tartil, and Tilawati. The research follows a qualitative approach, using data collection techniques such as observation, interviews, and documentation. Data analysis is conducted through grounded theory analysis. The validation techniques applied include extended participation, persistent observation, and triangulation. The findings indicate that Darul Ulum Seputih Banyak Islamic Boarding School effectively integrates these five methods, combining them to enhance the learning experience. This varied approach contributes to a more engaging learning atmosphere, boosts students' understanding of tajweed, and improves their recitation quality and fluency in reading the Qur'an.